KOMPLEKSITAS LINGKUNGAN DAN REGULASI PEMERINTAH: IMPLIKASINYA TERHADAP KINERJA PERBANKAN DI JAWA TIMUR - Sabihaini, Sabihaini; Hadiwidjojo, Djumilah; Djumahir, Djumahir; Rahayu, Mintarti (Jurnal Keuangan dan Perbankan, 2012)
This research was designed to describe the causal relationships between environmental complexity, governmentregulation, diversification levels, and performance. This research was conducted toward banking industryin East Java, in which the research samples were the top ten (10) well performed national commercial banks.The analysis was performed using Structural Equation Modeling (SEM). The research shows that: (1) thehigher environmental complexity level, the diversification made by the bank toward its major function wasgetting further or business activities of the bank was tend to be fee-based income activities and in fact increasebanks performance; (2) banking industry were encouraged to focus on its major function as intermediarycorporation due to intense support of government and reserve bank of Indonesia. However, the banking performancewas getting lower if the support of government and reserve bank of Indonesia on the main function of thebank (credit distribution) was getting higher. This investigation suggest that control system was needed inorder to increase the main function of the bank without increasing its risks.